(untitled) (Nepal Journal of Epidemiology, 2013)
I am writing in context to an article recently been published in the Journal of Drug Delivery and Therapeutics, Volume 3, Issue 4, July-August 2013 entitled ‘’Medications For Anxiety: A Drug Utilization Study In Psychiatry Outpatients From A Tertiary Care Centre Of Eastern India’4. http://jddtonline.info/index.php/jddt/article/view/574 I was very shocked to see that the above article is plagiarized from one of my paper which is the most popular article 53475 views till 21st July 2013 in NJE, ‘’Medications for Anxiety: A Drug Utilization Study In Psychiatry Inpatients From A Tertiary Care Centre of Western Nepal’’5 published in Nepal Journal of Epidemiology on September 2011. http://nepjol.info/index.php/NJE/article/view/5753 DOI: http://dx.doi.org/10.3126/nje.v3i3.9190 Nepal Journal of Epidemiology 2013;3(3): 277-278